(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In modern linguistics, the challenge of translating terms and identifying their associated variants is extensively researched. The field of construction terminology is expanding along with technological advancements, and difficulties related to word translation are receiving particular attention. The selection of suitable translation techniques results in the accurate understanding of the content.